Kinematic analysis of the upper limb at different impact heights in baseball batting - Tago, T.; Ae, M.; Tsuchioka, D.; Ishii, N.; Wada, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to investigate the change in the upper limb motion to three different hitting areas of the strike zone: high, middle, and low. Subjects were ten right-handed male skilled batters of a university baseball team. Data were collected using a three dimensional automatic motion analysis system (Vicon 612). The joint angles of the upper limbs were computed. Comparison of the hitting in the high area vs. low area revealed that to hit the ball in the low area the batter more extended his left elbow, and flexed more his both shoulders and horizontal adduction angle of the left shoulder was large at the phase of the Left upper arm parallel (LUP). At the impact phase he flexed his left elbow more, adduction angle of the left shoulder was small in the case of the high area than the case of the low area. The opposite tendency to the high area was observed in the case of the low area.